Characterization of Unripe Grapes (Vitis vinifera L.) and Its Use to Obtain Antioxidant Phenolic Compounds by Green Extraction - Bayram, Yuksel; Elgin Karabacak, Cigdem (Frontiers in Sustainable Food Systems, 2022)
Thinning pruning is a process in modern viticulture to improve product quality when grapes are still in the immature fruit stage. Unripe grapes, which are waste, are mostly consumed locally as verjuices to meet domestic demand. This study aims to optimize a more efficient “green” technique for the extraction of total phenolic compounds (TPC) and antioxidant capacity (AC) from three varieties of unripe grape juice by response surface method (RSM) using ultrasound-assisted extraction (UAE). The influence of temperature (25–65°C) and extraction time (5–30 min) on total phenolic content (TPC) and antioxidant capacity (DPPH and CUPRAC) was investigated. In this study, physicochemical properties, mineral composition, phenolic and organic acid components of three different verjuices were also investigated. As a result, the optimal extraction points for extraction time (12 min) and temperature (30°C) were determined. All independent variables were found to be significantly effective on TPC and AC content during UAE. Verjuices are a rich source of antioxidants, phenols, organic acids, minerals, and vitamin C. This study is expected to contribute to the evaluation of unripe grape wastes, which are very rich in bioactive components, and to increase its economic potential by expanding local production, thus contributing to sustainable agri-food processing.